Education-Based Preaching in Urban Society - Abdullah Sattar; Najmy Hanifah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The phenomenon of urban communities experiencing a shift in religious values requires a more adaptive and contextual approach to da'wah. Education-based da'wah is a strategic solution to systematically and sustainably ground the teachings of Islam. This study aims to explore the characteristics of educational da'wah carried out by Ustadz Nur Hidayat, a practitioner of Islamic education in Surabaya and Sidoarjo. The method used in this research is descriptive qualitative with a media text analysis approach. Primary data is obtained from Ustadz Nur Hidayat's book entitled Success Tips for Pioneering, Managing, and Developing Islamic Schools, while secondary data comes from his Instagram digital content. The analysis techniques used include content analysis and critical discourse analysis. The results showed that the educational da'wah developed by Ustadz Nur Hidayat emphasizes character building, internalization of Islamic values, and a humanist approach in the learning process. Da'wah is not only delivered through lectures, but also through nurturing, exemplary, and a structured education system. This approach has proven to be effective in responding to the challenges of urban society and has contributed significantly to the formation of a generation of Muslims who are faithful, knowledgeable, and noble.